A Direct Collaborative Network Intrusion Detection System for IoT Networks Integration - Pedroso, Carlos; Batista, Agnaldo; Brisio, Samuel; R., Rodrigues S.; Santos, Aldri (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2024.1354, 2024)
Integrating thousands of smart devices over the various IoT domains will require the devices to deliver services free of threats. Although intrusion detection systems (IDS) offer a multi-layer of protection to IoT networks, they commonly operate in isolation, thus restraining their application in integrated environments. In this context, collaboration among IDS emerges as an alternative to enhance intrusion detection, relying on their knowledge about faced threats. However, collaborative IDS (CIDS) generally exchange messages through centralized entities, disregarding direct communication among IDS. This work proposes a collaborative network IDS (C-NIDS) that integrates standalone NIDS for sharing information about detected and mitigated threats, improving overall intrusion detection. Evaluation results showed that C-NIDS achieved an attack detection rate of 99%, enhancing the attack mitigation by up to 50% compared to non-collaborative scenarios.